2016
DOI: 10.1155/2016/7590396
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Barbed Sutures and Standard Sutures with regard to Wound Cosmesis in Panniculectomy and Reduction Mammoplasty Patients

Abstract: Cosmesis is a vital concern for patients undergoing plastic and reconstructive surgery. Many variations in wound closure are employed when attempting to minimize a surgical scar's appearance. Barbed sutures are one potential method of achieving improved wound cosmesis and are more common in recent years. To determine if barbed sutures differ from nonbarbed in wound cosmesis, we conducted a single-blinded, randomized, controlled trial of 18 patients undergoing bilateral reduction mammoplasty or panniculectomy. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
2
1
0
Order By: Relevance
“…But in our study, there was no statistically significant difference in scar cosmesis as compared by Vancouver scar scale and POSAS (observer and patient scar scale) between the barbed and the non-barbed suture groups. Our findings were similar to studies by Kristen Aliano et al, Amy P Murtha et al, Rubin et al and Grigoryants et al [4][5][6][7]. As our study evaluated the scar for only three months, a prolonged follow up is further required to evaluate the scar after remodelling.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…But in our study, there was no statistically significant difference in scar cosmesis as compared by Vancouver scar scale and POSAS (observer and patient scar scale) between the barbed and the non-barbed suture groups. Our findings were similar to studies by Kristen Aliano et al, Amy P Murtha et al, Rubin et al and Grigoryants et al [4][5][6][7]. As our study evaluated the scar for only three months, a prolonged follow up is further required to evaluate the scar after remodelling.…”
Section: Discussionsupporting
confidence: 91%
“…In our study the time taken for barbed suture was less than conventional absorbable sutures and the difference was statistically significant. Similar results were seen in studies done by Koide et al, Kristen Aliano et al, Grigoryants et al, Jeremy P. Warner et al and Blacam et al [3,4,[7][8][9]. Jandali et al, found that using barbed sutures reduced the operative time of unilateral breast reconstruction significantly, but no significant difference was seen in the operative time of bilateral breast reconstruction [10].…”
Section: Discussionsupporting
confidence: 81%
“…30 On the other hand, a prospective study conducted by Aliano et al showed that standard sutures increase the risk of tissue ischemia due to increased tension at knotted loops compared to barbed sutures. 44,[53][54][55] Furthermore, excessive pressure within the tissue can produce enzymatic degradation which induces loss of wound strength and higher incidence of wound dehiscence. 54,56,57 Consequently, tight suturing has demonstrated compromised blood flow and consequent tissue necrosis.…”
Section: Safety Resultsmentioning
confidence: 99%